Structure–activity investigation of the potentiating effect of cyano substitution on nitroaniline mutagenicity in the ames test. (27th November 2017) - Josephy, P. David; Dhanoa, Joban; Elzawy, George; Heney, Kayla; Petrie, Laurenne; Senis, Chantel
Abstract : 2, 6‐Dicyano‐4‐nitroaniline and 2‐cyano‐4‐nitroaniline (CNNA; 2‐amino‐5‐nitrobenzonitrile) are potent mutagens in the Ames test, even though unsubstituted nitroanilines (NAs) are no more than weak mutagens. These compounds are putative reduction products of many commercial azo dyes, including Disperse Blue 165, Disperse Blue 337, Disperse Red 73, Disperse Red 82, Disperse Violet 33, and Disperse Violet 63. We have examined the mutagenicity in strains TA98 and YG1024 of a series of commercially‐available isomers of CNNA, and some related compounds, to probe the relationship between structure and genotoxic activity in this class of compounds. The potentiating effect of the cyano substituent is seen in many cases; e.g. 2‐amino‐4‐nitrobenzonitrile is a much more potent mutagen than 3‐NA. 2, 4‐Dinitrobenzonitrile is also highly mutagenic. Possible mechanisms for the "cyano effect" are considered, with respect to the likely structures of cyanonitroaniline‐DNA adducts and the roles of the enzymes (nitroreductase and acetyl CoA:arylamine N ‐acetyltransferase) believed to be involved in the activation of nitroaromatic compounds. Environ. Mol. Mutagen. 59:114–122, 2018. © 2017 Wiley Periodicals, Inc.